A literary history of medicine the ʿUyūn al-anbāʾ fī ṭabaqāt al-aṭibbāʾ of Ibn Abī Uṣaybiʿah - Ibn-Abī-Uṣaibiʿa, Aḥmad Ibn-al-Qāsim ca. 1194-1270 (Brill, 2020)
A Literary History of Medicine' by the Syrian physician Ibn Abi Usaybi'ah (d. 1270) is the earliest comprehensive history of medicine. It contains biographies of over 432 physicians, ranging from the ancient Greeks to the author's contemporaries, describing their training and practice, often as court physicians, and listing their medical works; all this interlaced with poems and anecdotes. These volumes present the first complete and annotated translation along with a new edition of the Arabic text showing the stages in which the author composed the work. Introductory essays provide important background. The reader will find on these pages an Islamic society that worked closely with Christians and Jews, deeply committed to advancing knowledge and applying it to health and wellbeing.
Keywords: Ibn-Abī-Uṣaibiʿa, Aḥmad Ibn-al-Qāsim -- ca. 1194-1270 -- ʿUyūn al-anbāʾ fī ṭabaqāt al-aṭibbāʾ; Aufsatzsammlung